THE CONCEPT OF COMPETITION IN BUSINESS FEASIBILITY STUDY - Hafni Nainggolan (Proceeding International Seminar of Islamic Studies, 2023)
Business competition is a natural thing in the industry. Businesses must be able to set the right marketing strategy to survive and win the competition. The existence of competition caused by many factors encourages business people to be able to maintain their business by implementing various business strategies.  The type of research method used in this research is by collecting data or information through primary data and also through literature (Library Research), namely research carried out with literature studies, the internet, and so on that are appropriate and relevant to the problem discussed. Business competition presents a variety of benefits for business people that are often unexpected and numerous. Competition between brands, products, competition and generic needs created due to the scarcity of resources where geographical variation occurs. A business feasibility study is to study in depth about an activity, business, or business that will be carried out in order to determine whether or not the business is feasible to run. A competitor is a business that produces or sells goods or services that are the same or similar to the products offered. Identification of competitors includes the type of product offered, the size of the market that competitor’s control, and others. In general, attacking a competitor consists of, the strategy of attacking a weak competitor first, a direct competitor attacking a strong opponent, a guerrilla strategy, a defensive strategy.